Wednesday

April 23, 2014

April 23, 2014

Posted by **Tori** on Monday, December 3, 2012 at 2:41am.

2x-3y-2z=4

(1/4)x-(2/5)y+(3/4)z=(-1/3)

-2x+1.3y-3z=5

Thank you so much! :)

- Pre-Calc -
**Damon**, Monday, December 3, 2012 at 3:30am2x-3y-2z=4

(1/4)x-(2/5)y+(3/4)z=(-1/3)

-2x+1.3y-3z=5

==============================

Google Gauss Jordan reduction

use all integers or fractions

2 -3 -2 4

1/4 -2/5 3/4 -1/3

-2 13/10 -3 5

Divide row 1 by 2

1 -3/2 -1 2

1/4 -2/5 3/4 -1/3

-2 13/10 -3 5

Add (-1/4 * row1) to row2

1 -3/2 -1 2

0 -1/40 1 -5/6

-2 13/10 -3 5

Add (2 * row1) to row3

1 -3/2 -1 2

0 -1/40 1 -5/6

0 -17/10 -5 9

Divide row2 by -1/40

1 -3/2 -1 2

0 1 -40 100/3

0 -17/10 -5 9

Add (17/10 * row2) to row3

1 -3/2 -1 2

0 1 -40 100/3

0 0 -73 197/3

Divide row3 by -73

1 -3/2 -1 2

0 1 -40 100/3

0 0 1 -197/219

Add (40 * row3) to row2

1 -3/2 -1 2

0 1 0 -580/219

0 0 1 -197/219

Add (1 * row3) to row1

1 -3/2 0 241/219

0 1 0 -580/219

0 0 1 -197/219

Add (3/2 * row2) to row1

1 0 0 -629/219

0 1 0 -580/219

0 0 1 -197/219

- Pre-Calc -
**Damon**, Monday, December 3, 2012 at 3:44amI used this:

http://www.gregthatcher.com/Mathematics/GaussJordan.aspx

- Pre-Calc -
**Tori**, Monday, December 3, 2012 at 4:16amOMG thanks you so much!

**Related Questions**

pre-calc - solve each system of equations using matrices x+2y-3z=0 2x-4y=z=-7 -...

Urgent please help! matrices - solve using matrices x+3y-3z=12 3x-y+4z=0 -x+2y-z...

Matrices (math) - 0.433= (45.6*A) + (3.152*B) 0.3363= (11.92*A) + (37.675*B) ...

pre calc - how do u solve for x and y of x+2y=7 2x+y=8 using matrix without ...

Math (matrices) - No one answered my matrix question. Let me rephrase: Let A, B...

pre calc - the hour hand of a clock is 5 inches long and the minute hand is 6 ...

Pre-Calculus - Is it possible to factor x^3 - 9x^2 + 24x - 20 and solve for x by...

Math - I have a few questions about T-Matrix. In excel, I am suppose to work ...

Pre Calc - x^2+y=9, x-y+3=0. Need to solve using substitution method.

Pre Calc - x^2+y=9, x-y+3=0. Need to solve using substitution method.